Strategi Pengembangan Peran Penyuluh Pertanian Lapang di Provinsi Banten - Narso Narso; Amiruddin Saleh; Pang S Asngari; Pudji Muljono (Jurnal Penyuluhan, 2012)
This research aim was to formulate priority of strategy development the role of agriculture extension agent in Banten. To determine the priority of strategy development the role of agriculture extension agent used SWOT and AHP. Result of research indicated that the priority of development Strategy of role the agriculture extension agent in Banten were: (1) Improving the quality of human resouces of extension agent by diklat from other institution to get the ability, knowledge, and skill; (2) Improving of quality of counselling and cooperation with the relevant institution by the existence of fundamental duty clarity and function; (3) Product marketing competitive agriculture by maximizing role of group of farmer; (4) Optimalization of agriculture development with the guarantee of invitation regulation; and (5) Exploiting technology to support the agriculture extinsion program.Keywords: strategy, role, development, agriculture extension agent